Pentraxin‐3 level at admission is a strong predictor of short‐term mortality in a community‐based hospital setting. (8th September 2014) - Bastrup‐Birk, S.; Munthe‐Fog, L.; Skjoedt, M.‐O.; Ma, Y. J.; Nielsen, H.; Køber, L.; Nielsen, O. W.; Iversen, K.; Garred, P.
Abstract Background The pattern recognition molecule pentraxin‐3 (PTX3) is a novel potential marker of prognosis, as elevated levels are associated with both disease severity and mortality in patients with a wide range of conditions. However, the usefulness of PTX3 as a prognostic biomarker in a general hospital setting is unknown. Patients and methods The study cohort consisted of 1326 unselected, consecutive patients (age >40 years) admitted to a community hospital in Copenhagen, Denmark. Patients were followed until death or for a median of 11.5 years after admission. The main outcome measure was all‐cause mortality. Serum samples collected from patients at admission and from 192 healthy control subjects were quantified for PTX3 level by enzyme‐linked immunosorbent assay. Results PTX3 was elevated in patients (median 3.7 ng mL−1, range 0.5–209.8) compared with healthy nonhospitalized subjects (median 3.5 ng mL−1, range 0.0–8.3; P = 0.0003). Elevated PTX3 levels, defined as above the 95th percentile of the concentration in healthy subjects, were associated with increased overall mortality during the study (P < 0.0001). This increase in mortality was greatest in the short term, with an unadjusted hazard ratio (HR) of 6.4 [95% confidence interval (CI) 3.8–11.0] at 28 days after admission, compared to 1.7 (95% CI 1.4–2.0) at the end of follow‐up. These results were still significant after adjustment for age, gender and glomerular filtration rate: adjusted HR of 5.0 (95% CI 2.9–8.8) and 1.4 (95% CI 1.2–1.8), respectively. Conclusion These results suggest that PTX3 could be a widely applicable marker of short‐term mortality in hospitalized patients and may be useful in the initial risk stratification.